Mediating Role Of Tourist Satisfaction On Image And Tourist Loyalty Of Local Food In Penang Island, Malaysia - Abhari, Sara (2023)
Destination food image and local cuisines can be considered significant aspects from the perspective of tourism that play a substantial role in tourist satisfaction and loyalty intentions. Despite ever-increasing research and academic recommendation toward the role of local food in tourism, there are still a contextual gap and a lack of theoretical argument in Malaysian tourism research on the concept of local food images, halal awareness, tourist satisfaction, and loyalty. In Penang Island tourism, there is a lack of research in identifying and learning components of local food image in tourism marketing, the contribution of cultural value, the role of heritage, and religion (halal awareness). This study attempts to investigate the multidimensional construct of local food images, considering the halal awareness and beliefs, and assessed their impact in Penang Island tourism industry as a gastronomy tourism destination on intention to repurchase, intentions to recommend (Word of Mouth), and Electronic Word of Mouth. In addition, the mediating effect of tourist satisfaction on this relationship has been examined. This study was designed as a quantitative method, data collection was conducted by self-administrative questionnaire. It was a cross-sectional study and the random sampling technique was employed. In total, 332 questionnaires were returned from respondents, and only 329 completed questionnaires were found usable for data analysis. The SmartPLS software version 3.2 was used to analyse the data, and Partial Least Squares Structural Equation Modelling (PLS-SEM) was applied.